Comparative transcriptome profiling of susceptible and tolerant citrus species at early and late stage of infection by “Candidatus Liberibacter asiaticus” - Gao, Chenying; Li, Cuixiao; Li, Ziyi; Liu, Yaoxin; Li, Jiaming; Guo, Jun; Mao, Jiana; Fang, Fang; Wang, Cheng; Deng, Xiaoling; Zheng, Zheng (Frontiers in Plant Science, 2023)
Citrus Huanglongbing (HLB), caused by “Candidatus Liberibacter asiaticus” (CLas), is the most destructive disease threatening global citrus industry. Most commercial cultivars were susceptible to HLB, although some showed tolerant to HLB phenotypically. Identifying tolerant citrus genotypes and understanding the mechanism correlated with tolerance to HLB is essential for breeding citrus variety tolerance/resistance to HLB. In this study, the graft assay with CLas-infected bud were performed in four citrus genotypes, including Citrus reticulata Blanco, C. sinensis, C. limon, and C. maxima. HLB tolerance was observed in C. limon and C. maxima, while C. Blanco and C. sinensis were susceptible to HLB. The time-course transcriptomic analysis revealed a significant variation in differentially expressed genes (DEGs) related to HLB between susceptible and tolerant cultivar group at early and late infection stage. Functional analysis of DEGs indicated that the activation of genes involved in SA-mediated defense response, PTI, cell wall associated immunity, endochitinase, phenylpropanoid and alpha-linolenic/linoleic lipid metabolism played an important in the tolerance of C. limon and C. maxima to HLB at early infection stage. In addition, the overactive plant defense combined with the stronger antibacterial activity (antibacterial secondary and lipid metabolism) and the suppression of pectinesterase were contributed to the long-term tolerance to HLB in C. limon and C. maxima at late infection stage. Particularly, the activation of ROS scavenging genes (catalases and ascorbate peroxidases) could help to reduce HLB symptoms in tolerant cultivars. In contrast, the overexpression of genes involved in oxidative burst and ethylene metabolism, as well as the late inducing of defense related genes could lead to the early HLB symptom development in susceptible cultivars at early infection stage. The weak defense response and antibacterial secondary metabolism, and the induce of pectinesterase were responsible for sensitivity to HLB in C. reticulata Blanco and C. sinensis at late infection stage. This study provided new insights into the tolerance/sensitivity mechanism against HLB and valuable guidance for breeding of HLB-tolerant/resistant cultivars.